1986
DOI: 10.1021/la00072a031
|View full text |Cite
|
Sign up to set email alerts
|

Structure and composition of a platinum(111) surface as a function of pH and electrode potential in aqueous bromide solutions

Abstract: Hl value. As shown in Figure 5, the shape of the qst curve on OG-400 and OG-25 is very similar to that on OG-700, the only difference being the fact that the break point slightly shifts to higher coverage of H20 from OG-700 to OG-400 and further to OG-25. Admittedly, there is a great difference between the qst curves on OG-700 and OG-IOOO.The reason why such a difference appears can be attributed to the fact that the CO content on OG-700 is as much as those on OG-25 and OG-400, in contrast to a smaller value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
51
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 3 publications
9
51
3
Order By: Relevance
“…However, the STM images obtained at potentials lower than the sharp spike revealed that the Br adlayer was not the (4 · 4) structure proposed in Ref. [9], but an incommensurate structure. Independently, Orts et al studied the properties of strongly adsorbed bromine monolayers formed either by bromide or by bromine adsorption on a Pt(1 1 1) surface, using cyclic voltammetry, CO charge-displacement method and ex situ STM imaging [11].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, the STM images obtained at potentials lower than the sharp spike revealed that the Br adlayer was not the (4 · 4) structure proposed in Ref. [9], but an incommensurate structure. Independently, Orts et al studied the properties of strongly adsorbed bromine monolayers formed either by bromide or by bromine adsorption on a Pt(1 1 1) surface, using cyclic voltammetry, CO charge-displacement method and ex situ STM imaging [11].…”
Section: Introductionmentioning
confidence: 53%
“…First, we used 0.1 M HClO 4 as the supporting electrolyte. In these solutions, the substitution of hydrogen by bromide at the Pt(1 1 1) surface takes place in a very narrow potential range, as described previously [6][7][8][9][10][11]. The corresponding voltammetric peaks are very sharp, and the integration of such curves is subjected to a non-negligible error.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This trend is in accordance with the shift observed in case of single crystal electrode. 33,35 Figs. 4d, 4e and 4f show the CVs of Pt-NC, Pt-CO and Pt-PC, respectively, recorded with 1 × 10 −3 M Br − ions in the potential range of 0.06-1.2, 1.4, 1.6 V. The Pt oxidation and reduction features of the CVs are suppressed when compared to that observed with halide-free electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Feliu et al, Abruna et al, and others have extensively investigated the influence of halides (I − , Br − , Cl − ) on platinum single crystal electrodes. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most of the available surface sensitive techniques were used to elucidate adsorbate coverage and structure. Such techniques, including auger electron spectroscopy (AES), low energy electron diffraction (LEED), second harmonic generation (SHG), surface X-ray scattering (SXS), electrochemical scanning tunneling microscope (ESTM) 31,34 and electrochemical quartz crystal microbalance (EQCM), used to investigate anion adsorption have offered significant insight on the dependence of adsorption process on exposed single crystal orientations.…”
mentioning
confidence: 99%